Analisis Rasio Likuiditas dan Solvabilitas dalam Meningkatkan Kinerja Keuangan Baitul Maal Wattamwiil Mu’amalah Syariah Tebuireng - Sumiyati Sumiyati; Meta Ardiana (JFAS : Journal of Finance and Accounting Studies, 2020)
This study aims to improve the financial performance of BMT Mu'amalah Syariah Tebuireng by using an analysis of liquidity and solvency ratios. The data used in this study are primary and secondary data obtained from the financial statements of BMT Mu'amalah Syariah Tebuireng for five years. While the method of data analysis used is descriptive qualitative which is analyzed using financial ratios based on the achievement of the Minister of Cooperative regulation, it can be concluded that the liquidity ratios are calculated using the current ratio formula that is in poor condition. Whereas the solvency ratio is calculated by the formula of debt to equity ratio and the ratio of debt to assets in the criteria is not good.